2020
DOI: 10.1126/scitranslmed.aaw9522
|View full text |Cite
|
Sign up to set email alerts
|

Immune system development varies according to age, location, and anemia in African children

Abstract: Children from low- and middle-income countries, where there is a high incidence of infectious disease, have the greatest need for the protection afforded by vaccination, but vaccines often show reduced efficacy in these populations. An improved understanding of how age, infection, nutrition, and genetics influence immune ontogeny and function is key to informing vaccine design for this at-risk population. We sought to identify factors that shape immune development in children under 5 years of age from Tanzania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 70 publications
2
59
0
Order By: Relevance
“…These examples along with a review on this possible mechanism of fingerprinting in nine pathogens, including Pf ( Vatti et al, 2017 ), indicate that the phenomenon of ‘original antigenic sin’ which is known in the context of seasonal influenza vaccine goes beyond virus diseases. Our findings add to the increasing knowledge that – across the taxa - the personalized immune and metabolic status and history of pathogen exposure may affect vaccine take and the potential to elicit high levels of protection in vaccinated populations ( Vatti et al, 2017 ; Tsang et al, 2020 ; Hill et al, 2020 ; Baraniak et al, 2019 ).…”
Section: Discussionmentioning
confidence: 58%
“…These examples along with a review on this possible mechanism of fingerprinting in nine pathogens, including Pf ( Vatti et al, 2017 ), indicate that the phenomenon of ‘original antigenic sin’ which is known in the context of seasonal influenza vaccine goes beyond virus diseases. Our findings add to the increasing knowledge that – across the taxa - the personalized immune and metabolic status and history of pathogen exposure may affect vaccine take and the potential to elicit high levels of protection in vaccinated populations ( Vatti et al, 2017 ; Tsang et al, 2020 ; Hill et al, 2020 ; Baraniak et al, 2019 ).…”
Section: Discussionmentioning
confidence: 58%
“…Considering the late arrival of COVID-19 in Africa and media speculation that Africans immune system may be resistant to the survival of the virus supported by the temperate weather, a recent study published in Science Translational Medicine shed more insight as to why Africa healthcare leaders should take more proactive measures in curtailing the spread of the virus [15]. In this study,…”
Section: Challenges/ Way Forwardmentioning
confidence: 93%
“…Recently our group demonstrated that age, location and iron status influence the immune system development of children as well as vaccine-induced responses to the most advanced malaria vaccine candidate, the RTS,S [13]. Additionally, communicable and non-communicable diseases have been implicated in suboptimal vaccine-induced responses [14] Chronic, asymptomatic viral infections at time of immunization might contribute to reduced magnitude and longevity of vaccine-induced immune responses [15][16][17].…”
Section: Introductionmentioning
confidence: 99%